LMX1B missense-perturbation of regulatory element footprints disrupts serotonergic forebrain axon arborization - Brent Eastman; Nobuko Tabuchi; Xinrui L. Zhang; William C. Spencer; Evan S. Deneris (Proceedings of the National Academy of Sciences, 2025)
Pathogenic coding mutations are prevalent in human neuronal transcription factors (TFs) but how they disrupt development is poorly understood. Lmx1b is a master transcriptional regulator of postmitotic Pet1 neurons that give rise to mature serotonin (5-HT) neurons; over two hundred pathogenic heterozygous mutations have been discovered in human LMX1B, yet their impact on brain development has not been investigated. Here, we developed mouse models with different LMX1B DNA-binding missense mutations. Missense heterozygosity broadly altered Pet1 neuron transcriptomes, but expression changes converged on axon and synapse genes. Missense heterozygosity effected highly specific deficits in the postnatal maturation of forebrain serotonin axon arbors, primarily in the hippocampus and motor cortex, which was associated with spatial memory defects. Digital genomic footprinting (DGF) revealed that missense heterozygosity caused complete loss of Lmx1b motif protection and chromatin accessibility at sites enriched for a distal active enhancer/active promoter histone signature and homeodomain binding motifs; at other bound Lmx1b motifs, varying levels of losses, gains, or no change in motif binding and accessibility were found. The spectrum of footprint changes was strongly associated with synapse and axon genes. Further, Lmx1b missense heterozygosity caused wide disruption of Lmx1b-dependent GRNs comprising diverse TFs expressed in Pet1 neurons. These findings reveal an unanticipated continuum of Lmx1b missense-forced perturbations on Pet1 neuron regulatory element TF binding and accessibility. Our work illustrates DGF’s utility for gaining unique insight into how expressed TF missense mutations interfere with developing neuronal GRNs.